Some Results on Oxygen Isotope and Stratigraphic Analyses of Firn in Mizuho Plateau, East Antarctica - Watanabe, Okitsugu; Kato, Kikuo; Satow, Kazuhide (1981)
P(論文) Oxygen isotope (δ^<18>O) and stratigraphic analyses of the 2m deep pits and the 10m deep cores from the coast to the high-inland region of Mizuho Plateau have been done. A seasonal diagram of δ^<18>O of drifting snow in connection with the elevation was obtained from the δ^<18>O values of fallen snow and drifting snow. The regional characteristics of the relations between the δ^<18>O profiles and the firn layering structures were examined. The seasonal cycles of δ^<18>O are only found in the δ^<18>O profiles in the firn of the coastal region and in the specified places of the katabatic slope region. The δ^<18>O profile in the most of the katabatic slope region is largely controlled by the season of formation of the surface snow layer and the snow metamorphosis such as the formation of loose and hard depth hoar. Similar tendencies are found in the profiles of the running means of δ^<18>O in the cores of the costal region and of the katabatic slope region, respectively. These tendencies may reflect the change of glaciological environment spread over each region. departmental bulletin paper